2014
DOI: 10.1080/01635581.2013.878734
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Case-Cohort Study of Brain Cancer in Poultry and Control Workers

Abstract: We conducted an exploratory study to investigate which exposures (including poultry oncogenic viruses) are associated with brain cancer in poultry workers. A total of 46,819 workers in poultry and nonpoultry plants from the same union were initially followed for mortality. Brain cancer was observed to be in excess among poultry workers. Here we report on a pilot case-cohort study with cases consisting of 26 (55%) of the 47 brain cancer deaths recorded in the cohort, and controls consisting of a random sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…A potential is present for information bias for the risk factors in Felini et al (46) and in Gandhi et al (48). The respondents for the risk factors for the cases were of necessity only next of kin (the cases were already dead).…”
Section: Epidemiology Regarding Cancer and Mortalitymentioning
confidence: 98%
See 4 more Smart Citations
“…A potential is present for information bias for the risk factors in Felini et al (46) and in Gandhi et al (48). The respondents for the risk factors for the cases were of necessity only next of kin (the cases were already dead).…”
Section: Epidemiology Regarding Cancer and Mortalitymentioning
confidence: 98%
“…On the other hand, authors can still indicate the numbers of risk factors tested so that the, albeit partial, list of significant risk factors declared in the abstract is put into perspective; this was not done in any of the four primary studies reviewed. In addition, Gandhi et al (48) found only 13 significant risk factors even at their unadjusted alpha of 5%, and listing all 13 might well have been possible. However, the abstract listed only 5 of the 13 (including the only one related to poultry) without warning of another 8 significant risk factors or that the questionnaire from which the risk factors were derived contained 646 questions.…”
Section: Epidemiology Regarding Cancer and Mortalitymentioning
confidence: 99%
See 3 more Smart Citations